Evaluation of Organic Vinasse and Bagazo Sugar Cane Sugar for the Organic production of rabanito (Raphanus sativus L.) - Gálvez Torres, Edwin (2019)
The research deals with sugarcane residues. Its objective is to use it as fertilizer to minimize the use of synthetic fertilizers. To obtain this fertilizer, composting was prepared with 16,5 kg of stubble, 16,5 kg of guano guinea pig and 11 kg of bagasse and 11 liters of vinasse. The statistical model of Completely Random Block Design was used, which consists of ve treatments: T1 with 0, T2 with 10, T3 with 15, T4 with 20 and TT5 with 25 g. and it was evaluated in laboratory and chemical analysis. The statistical analysis that was applied was the analysis of variance and Duncan. It was determined that the T4 exceeded in yield with 15,39 tn / ha,weight per plant 44,66 g, plant length with 25,16 cm, equatorial diameter with 3,6090 cm, polar diameter with 4,80 cm, root length with 10,35 cm. In chemical analysis, T1 stood out with 110 iron; T1 with 89 zinc; T5 with 61 copper and T4 with 67 boron per parts per million. Like T2 with 6,86 nitrogen; T1 with 0,68 phosphorus; T2 with 5,51 potassium; T1 with 5,11 calcium; T2 with 0,5 mg and T2 with 1,06 % sodium.